Profitability: Third Party Funds and Credit Risk Study on Indonesian Digital Banking - Raden Bagus Faizal Irany Sidharta; Rini Anggriani; Isra Dewi Kuntary Ibrahim; Noni Kezia Marchyta (Target : Jurnal Manajemen Bisnis, 2022)
With advances in technological development, people’s needs for fast and readily available services are on the rise. Therefore, many conventional banks started to develop their own brand of digital banking to accommodate these needs. This research is aimed to analyze the effect of third party funds (TPF) toward profitability and credit risk, effect of credit risk toward profitability, and indirect effect of third party funds toward profitability through credit risk by using path analysis method. This research shows that TPF do have a significantly negative effect toward credit risk and similar result of TPF toward profitability, a positive but insignificant effect of credit risk toward profitability, and lastly, TPF shows a direct effect toward profitability, which means that credit risk functioned as a partial mediation effect between TPF and profitability.